2019
DOI: 10.1186/s12889-019-7791-0
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal ideation and attempt among school going adolescents in Bhutan – a secondary analysis of a global school-based student health survey in Bhutan 2016

Abstract: BackgroundSuicide is one of the leading causes of death and Disability Adjusted Life Years (DALYs) worldwide. The economic, emotional and human cost of suicidal behaviour to individuals, families, communities and society makes it a serious public health issue. We aim to determine the prevalence and factors associated with self-reported suicidal behaviour (suicidal ideation and attempt) among school going adolescents (13–17 years).MethodsThis is a secondary analysis of a nationally representative data for Bhuta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 29 publications
2
32
0
1
Order By: Relevance
“…Nepalese adolescents have high rates of health and social vulnerabilities and psychosocial problems, and they are especially higher among girls. Furthermore, the psychosocial well-being of adolescents is also affected by their SES in Nepal [84]. Despite efforts to reduce gender inequality, women/girls in Nepal are still marginalized in society (e.g., discrepancy in the available roles, priorities, opportunities, and resources) which affects their health, development and well-being [85].…”
Section: Discussionmentioning
confidence: 99%
“…Nepalese adolescents have high rates of health and social vulnerabilities and psychosocial problems, and they are especially higher among girls. Furthermore, the psychosocial well-being of adolescents is also affected by their SES in Nepal [84]. Despite efforts to reduce gender inequality, women/girls in Nepal are still marginalized in society (e.g., discrepancy in the available roles, priorities, opportunities, and resources) which affects their health, development and well-being [85].…”
Section: Discussionmentioning
confidence: 99%
“…In some Western countries, the reported prevalence of suicidal ideation was 12.1-22.0% and that of suicidal attempts was 1.0-7.6% [3][4][5][6][7]. However, low-and middle-income countries showed higher prevalence rates [8][9][10], and some Asian countries had equal or lower prevalence rates than those reported for Western countries [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found that adolescents connected to their parents were less likely to commit suicide (Kidd et al 2006), and parental support and supervision were linked to low suicidal ideation and attempt (Dema et al 2019;Peltzer and Pengpid 2017;Putra et al 2019). However, the recent study using data from 48 LMICs indicated that parental over-protection (i.e., too much parental care and monitoring) was associated with higher odds of suicidal ideation and suicide plan among adolescents (Kim 2019).…”
Section: Introductionmentioning
confidence: 97%
“…The reasons behind suicidal behaviors are complex and affected by a variety of risk factors at multiple levels. At the individual level, these factors include demographic characteristics: higher age, a few close friends (Peltzer and Pengpid 2017; Putra et al 2019; Uddin et al 2019); mental health disorders: depression, anxiety, poor self-esteem, loneliness (Itani et al 2017; Putra et al 2019; Shayo and Lawala 2019; Wilson et al 2012); lifestyle risk behaviors: drugs use, drinking, smoking (Almansour and Siziya 2017; Itani et al 2017; Peltzer and Pengpid 2015; Putra et al 2019); peer victimization: being violence, bullying victim, involved in the physical fight (Almansour and Siziya 2017; Dema et al 2019; Page and West 2011); and poor academic performance (Almansour and Siziya 2017). At the household level, parental separation, parental divorce, or poor family relationships are the key factors associated with suicidal behaviors (Hawton et al 2012; McMahon et al 2010).…”
Section: Introductionmentioning
confidence: 99%